Pelatihan Pembuatan Aplikasi Perpustakaan Digital Untuk SMK Tritech Informatika Medan Dengan Fliphtml Berbasis Web - Dedi Leman; Edy Victor Haryanto; Noprita Elisabeth S (Jurnal Pengabdian Masyarakat, 2024)
Tritech Informatics Vocational High School (SMK) Medan is a school located on Jalan Bayangkara Medan. The library administration implemented at Tritech Informatics Vocational School in Medan currently still applies conventional procedures. Digital libraries are economically more profitable than traditional libraries. This is because the existence of a digital library is able to share library book collections and makes it easier to find the book information needed and is able to facilitate services in the process of borrowing and returning books as well as making monthly reports. But there is also the most important thing, namely how library members or the public can immediately read books without having to borrow them, thereby making time and space more efficient because members don't have to worry about delays in returning books. With fliphtml and digital library web training, it will provide many conveniences for library staff. Apart from that, it also creates a systemized digital library so that there is no more loss or errors in storage or delays in returning physically borrowed books. It is hoped that this will help activities at the Medan Tritech Informatics Vocational School. This system training is very useful for ebooks that are still stored in school storage media and cannot be used until now.